1995
DOI: 10.1172/jci117949
|View full text |Cite
|
Sign up to set email alerts
|

Tissue plasminogen activator (tPA) inhibits plasmin degradation of fibrin. A mechanism that slows tPA-mediated fibrinolysis but does not require alpha 2-antiplasmin or leakage of intrinsic plasminogen.

Abstract: Thrombolysis is dramatically slower when high concentrations of lytic agent are used. This paradoxical observation, first described as "plasminogen steal," was originally believed to be due to depletion of extrinsic plasminogen and consequent leaching of clot-bound plasminogen. We report that administration of increasing concentrations of recombinant human tissue plasminogen activator (tPA) to fibrin gels resulted in Iysis rates that displayed a maximum, with significantly slower rates found at higher tPA, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The recommendable dosage of rt-PA in LIF is still being debated. In vitro studies have shown that rt-PA, but not urokinase, caused a dose-dependent inhibition of the fibrinolytic activity of plasmin with slower lysis rates at increasing rt-PA dosages [33]. In the present study, the recanalization rate did not differ between low-dose and high-dose rt-PA treatment; the mortality, however, was lower in cases of high-dose treatment despite the highest rate of lethal PH (n = 4/7).…”
Section: Discussionmentioning
confidence: 99%
“…The recommendable dosage of rt-PA in LIF is still being debated. In vitro studies have shown that rt-PA, but not urokinase, caused a dose-dependent inhibition of the fibrinolytic activity of plasmin with slower lysis rates at increasing rt-PA dosages [33]. In the present study, the recanalization rate did not differ between low-dose and high-dose rt-PA treatment; the mortality, however, was lower in cases of high-dose treatment despite the highest rate of lethal PH (n = 4/7).…”
Section: Discussionmentioning
confidence: 99%
“…4 The reason for the lack of effect of these thrombolytics at higher doses is not clear; however, at least for tPA, the hypothesis is that the drop-off in activity may be related to the "plasminogen-steal" effect, or depletion of available plasminogen, a phenomenon that appears to be associated with blood flow rates at the clot site and the concentration of plasminogen, the precursor to plasmin, on or near the surface of the clot. [23][24][25] Another possibility is that higher doses of tPA may inhibit the fibrinolytic action of plasmin. 24 However, because microplasmin appears to have a low affinity for fibrin 26 and acts directly to lyse a clot, 16 it is unlikely that the classic plasminogen-steal effect applies to its lack of effect at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Typical simulations were completed in less than 5 s on an SGI Indy workstation (175 MHz R4400 processor). By correlating ®brin loss predicted by a well-mixed model of ®brinolysis to dynamic measurements of lysis of dilute FITC-®brin under well-mixed conditions (Wu and Diamond, 1995b), the forward adsorption rates k i f for tPA, plasminogen, and plasmin, and the rates of plasmin-mediated lysis, k catW and k catN , were determined. Speci®cally, k f plm , k catW , and k catN , were determined by correlating ®brin loss to measurements of FITC-®brin¯uorescence dequenching in plasmin-mediated lysis for varying plasmin concentration (Wu and Diamond, 1995b).…”
Section: Heterogeneous Fibrinolysis Modelmentioning
confidence: 99%